Arabidopsis thaliana Yellow Stripe1-Like4 and Yellow Stripe1-Like6 localize to internal cellular membranes and are involved in metal ion homeostasis - Chu, Heng-Hsuan; Conte, Sarah S.; Chan Rodriguez, David; Vasques, Kenneth; Punshon, Tracy; Salt, David E.; Walker, Elsbeth L. (Frontiers in Plant Science, 2013)
Several members of the Yellow Stripe1-Like (YSL) family of transporter proteins are able to transport metal-nicotianamine (NA) complexes. Substantial progress has been made in understanding the roles of the Arabidopsis YSLs that are most closely related to the founding member of the family, ZmYS1 (e.g., AtYSL1, AtYSL2 and AtYSL3), but there is little information concerning members of the other two well-conserved YSL clades. Here, we provide evidence that AtYSL4 and AtYSL6, which are the only genes in Arabidopsis belong to YSL Group II, are localized to vacuole membranes and to internal membranes resembling endoplasmic reticulum. Both single and double mutants for YSL4 and YSL6 were rigorously analyzed, and have surprisingly mild phenotypes, in spite of the strong and wide-ranging expression of YSL6. However, in the presence of toxic levels of Mn and Ni, plants with mutations in YSL4 and YSL6 and plants overexpressing GFP-tagged YSL6 showed growth defects, indicating a role for these transporters in heavy metal stress responses.